Development of the WASAKA Learning Model on Heat and Temperature Topics for Higher Education - Lutfiyanti Fitriah; Ana Widya Ilahi; Masniah Masniah; Muhammad Akhsan Arif (Berkala Ilmiah Pendidikan Fisika, 2023)
Lecturers are required to carry out learning as well as professionally. Lecturers must apply student-centered learning models in lectures so students can study well. This research aimed to develop a valid WASAKA (Write, Analyze, Argue, Knowledge Development, and Act) learning model that can be implemented in the classroom and gets a good response from students who study heat and temperature in higher education. This research used Educational Design Research (EDR) research. The subjects of this study were 28 students studying heat and temperature in the Fundamental Physics course. Data collection techniques in this research were observation and an online survey using the Google form with the cross-sectional survey design method. The research instruments used were validation sheets, observation sheets, and response questionnaires. The data obtained were then analyzed using the Aiken formula and descriptive statistics. The results showed that the WASAKA learning model had content validity of 0.87-0.93 with valid categories; the average implementation of the model in terms of lecturer activities is 4.99 with a very good category; the average implementation of the model in terms of student activities is 4.87 with a very good category, and students gave a very good response to the model. This research concluded that the learning model developed was valid, implemented, and responded well by students. Thus, the learning model can be applied in Fundamental Physics lectures, especially in Higher Education heat and temperature topics.